A Simple Laboratory Technique for Comparing Performance of Baking Powders - Mohsin Ali, Tahira; Hasnain, Abid (Asian Journal of Chemistry, 2010)
A very simple and low cost laboratory technique that could be used on routine basis to monitor and control the quality of baking powders was studied. This technique did not require preparation of any dough or solution prior to analysis. Simply by measuring the volumetric flow rate of liberated CO2 gas; the baking powders with different leavening acid compositions could be compared and thereby classified into slow and fast acting baking powders.